Dostarlimab: A light of hope espied amidst an age-long combat against cancer - Gul, Areeba (Journal of the Pakistan Medical Association, 2023)
Madam, a recent study investigated if checkpoint blockade would be effectual in patients with mismatch repair-deficient (MMRd), locally advanced rectal cancer.1 Patients with MMRd stage II or III rectal adenocarcinoma- treated conventionally via surgery, radiation therapy and chemotherapy- received the intravenous medicament of single-agent dostarlimab, an anti-PD-1 monoclonal antibody, every three weeks for six months.1, 3 Extraordinarily, complete clinical remission was observed in 100% of the patients.1, 4 Twelve patients have undertaken the complete treatment, with an additional six month period of post-treatment follow up, and exhibited no sign of tumor on physical exam, MRI scans, endoscopy, PET scans, digital rectal examination, or biopsy.1 Hence, they were not required to partake in chemoradiotherapy or surgery.1, 4 Dostarlimab, a checkpoint inhibitor, has been utilized as a form of immunotherapy which worked in MMRd colorectal cancer cells amongst which the absence of a DNA repairing gene is observed.2, 4 Dr. Andrea Cercek, explains that ordinarily immunotherapy demonstrates a success rate of approximately 10% when used in colorectal cancer in advanced disease, as opposed to that of dostarlimab at 100%.2 Commonly, checkpoint inhibitors trigger reactions in 1 in 5 patients, and while the majority are easily handled, 3% to 5% suffer extreme complications that may cause difficulty in swallowing, masticating and muscle weakness..4 Another game-changer observed by Cercek et al. is the lack of clinical side-effects.1, 4 In rectal cancer, where arduous treatments can have enfeebling sequelae, comprising bowel, bladder and sexual disfunction, in addition to infertility and neural damage, dostarlimab may also be the key to a good quality of life post cancer survival.3,4 Due to the small sample size, however, there is little data on the efficacy of this treatment. Results, though promising, will require a bigger group of patients to add to their credibility. 3,4 Follow up-s spanning a lengthier period would ensure that there are no relapses or sideeffects and that the drug has proved remedial. 1, 3, 4 Furthermore, as suggested by Dr. Cercek, this hypothesis should be tested in other MMRd solid tumours such as stomach, pancreatic and bladder cancer, which have similar potential for successful immunotherapy.2 Dostarlimab’s previous success with endometrial cancer adds promise to this vision.5 The National Health Service in the UK, via the Cancer Drugs Fund, is offering dostarlimab to 100 women every year for endometrial cancer treatment, which costs $11,000 per dose.4, 5 ---Continue